The blood vasculature instructs lymphatic patterning in a SOX7‐dependent manner. (30th January 2023) - Chiang, Ivy K N; Graus, Matthew S; Kirschnick, Nils; Davidson, Tara; Luu, Winnie; Harwood, Richard; Jiang, Keyi; Li, Bitong; Wong, Yew Yan; Moustaqil, Mehdi; Lesieur, Emmanuelle; Skoczylas, Renae; et al.
Abstract: Despite a growing catalog of secreted factors critical for lymphatic network assembly, little is known about the mechanisms that modulate the expression level of these molecular cues in blood vascular endothelial cells (BECs). Here, we show that a BEC‐specific transcription factor, SOX7, plays a crucial role in a non‐cell‐autonomous manner by modulating the transcription of angiocrine signals to pattern lymphatic vessels. While SOX7 is not expressed in lymphatic endothelial cells (LECs), the conditional loss of SOX7 function in mouse embryos causes a dysmorphic dermal lymphatic phenotype. We identify novel distant regulatory regions in mice and humans that contribute to directly repressing the transcription of a major lymphangiogenic growth factor ( Vegfc ) in a SOX7‐dependent manner. Further, we show that SOX7 directly binds HEY1, a canonical repressor of the Notch pathway, suggesting that transcriptional repression may also be modulated by the recruitment of this protein partner at Vegfc genomic regulatory regions. Our work unveils a role for SOX7 in modulating downstream signaling events crucial for lymphatic patterning, at least in part via the transcriptional repression of VEGFC levels in the blood vascular endothelium. Synopsis: Blood endothelial cells guide patterning of lymphatic vasculature via expression of various signaling molecules. This study reports the role of the blood vascular endothelial‐specific transcription factor, SOX7, as a key driver of dorso‐lateral patterning of lymphatic vessels during development by repressing VEGFC transcription. SOX7 deletion in blood vascular endothelial cells in mice causes lymphoedema and ectopic lymphangiogenesis. Loss of SOX7 function upregulates Vegfc transcript levels in arterial endothelial cells. SOX7 represses VEGFC transcription via the Notch pathway and by directly binding to the Vegfc locus. Loss of SOX7 function expands the lymphatic endothelial cell progenitor pool and disturbs their distribution, similar to VEGFC gain‐of‐function. Abstract : SOX7 represses transcription of the lymphangiogenic factor VEGFC in the blood vascular endothelium to maintain proper patterning of lymphatic vessels.